2001
DOI: 10.1152/jappl.2001.91.4.1520
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory and aerobic changes after endurance training in a hypobaric hypoxic and warm environment

Abstract: Plasma volume (PV) expansion by endurance training and/or heat acclimatization is known to increase aerobic and thermoregulatory capacities in humans. Also, higher erythrocyte volume (EV) fractions in blood are known to improve these capacities. We tested the hypothesis that training in a hypobaric hypoxic and warm environment would increase peak aerobic power (VO(2)(peak)) and forearm skin vascular conductance (FVC) response to increased esophageal temperature (T(es)) more than training in either environment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 27 publications
5
72
0
Order By: Relevance
“…Blood volume fluctuates with seasonal variation of T a ; 5% expansion in the hottest months and ~3% contraction in the coldest months 56) . We recently reported that 3.5% PV expansion occurred after 10-d endurance training (at 60% VO 2max for 1 h/d) in warm environments (T a =30°C) with concomitant improvement of thermoregulatory responses 57) . More recently, Ichinose et al 59) suggested that the increases in blood volume and cardiac stroke volume after endurance training for 10 d are closely associated with the enhanced sensitivity of cutaneous vasodilation to increased T es during exercise in a hot environment.…”
Section: Blood Volume Expansionmentioning
confidence: 95%
See 2 more Smart Citations
“…Blood volume fluctuates with seasonal variation of T a ; 5% expansion in the hottest months and ~3% contraction in the coldest months 56) . We recently reported that 3.5% PV expansion occurred after 10-d endurance training (at 60% VO 2max for 1 h/d) in warm environments (T a =30°C) with concomitant improvement of thermoregulatory responses 57) . More recently, Ichinose et al 59) suggested that the increases in blood volume and cardiac stroke volume after endurance training for 10 d are closely associated with the enhanced sensitivity of cutaneous vasodilation to increased T es during exercise in a hot environment.…”
Section: Blood Volume Expansionmentioning
confidence: 95%
“…5). Since the reduction in each subject was significantly correlated with the increase in PV after training, they suggested that the stretch of baroreceptors due to PV expansion 57,58) was involved in the reduction. However, they also suggested that there was no causal relationship between the reduction in osmotic suppression of cutaneous vasodilation and plasma expansion but they were caused by different mechanisms associated with heat acclimation.…”
Section: Blunted Hyperosmotic Suppressions Of Thermoregulatory Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…After a subsequent 10-day training period in a hot condition (T a , 35°C), these responses improved further [27]. The increased SkBF and sweating responses are characterized by the early start of cutaneous vasodilation and sweating responses to increased T es [28,29] and the increased sensitivity to increase SkBF and sweat rate in response to an increased T es compared with before exercise training [28,29]. It is suggested that the mechanisms of the increase in thermoregulatory responses with exercise training are similar to those following acclimations to repeated heat exposures, including adaptations of the thermoregulatory center and thermoregulatory effectors [1,12] as well as an increase in VO 2max [30] and PV [28,31,32].…”
Section: Effects Of Exercise Training On Thermoregulation In Warm Andmentioning
confidence: 99%
“…Several longitudinal studies have reported that heat dissipative responses during exercise in a hot environment are enhanced when aerobic training is performed under hot or even cool to thermoneutral conditions by initially sedentary elderly individuals [30,60,84] and young individuals [27][28][29]. Thomas et al [30] reported that a 16-week aerobic training program increased VO 2max by ≥5% and advanced onset of cutaneous vasodilation in response to an increased mean body temperature during exercise in a hot environment (T a , 36°C) both in young and in elderly individuals.…”
Section: Effects Of Exercise Training On Thermoregulation In the Eldementioning
confidence: 99%